Fouling mechanisms of asphaltenes and fine solids on bare and electroless nickel-phosphorus coated carbon steel. (15th September 2019) - Gong, Lu; Wang, Jingyi; Zhang, Ling; Fattahpour, Vahidoddin; Mamoudi, Mahdi; Roostaei, Morteza; Fermaniuk, Brent; Luo, Jing-Li; Zeng, Hongbo
Graphical abstract: Highlights: Direct force measurements were applied to investigate fouling mechanisms. Obtained results revealed the driving forces in fouling phenomena. Bulk fouling tests were conducted to examine fouling and antifouling properties. Electroless nickel-phosphorus coating shows better antifouling performance. Abstract: Fouling is a critical issue faced by the chemical and oil industries in various operation processes, which has negative impact on the operational efficiency and generates significant economic losses, technical and environmental challenges. Investigating the interaction mechanisms between foulants (e.g., fine solids, asphaltenes) and different substrates is of both fundamental and practical importance in understanding the fouling mechanisms in chemical/petroleum engineering processes and developing antifouling strategies. In this work, atomic force microscope (AFM) colloidal probe technique was employed to directly quantify the interactions between silica or asphaltenes and selected substrates (i.e., carbon steel L80 and L80 with electroless nickel-phosphorus (EN) coating) in aqueous solutions. The effects of salinity, pH and presence of divalent ions (e.g., Ca 2+ ) on the surface interactions were investigated. The obtained force profiles showed that the interactions between silica or asphaltenes and L80 surface were more attractive than that between silica or asphaltenes and EN coating, in NaCl solutions. Bulk fouling tests in silica and asphaltenes-coated silica suspensions revealed that significant fouling of silica and asphaltenes were found on L80 substrates, while EN coating exhibited excellent antifouling performance. Our results provide useful insights into the fundamental understanding of the fouling mechanism of fine solids and asphaltenes, and the development of novel effective antifouling coatings in chemical and oil industries.